Green Coffee (Coffea arabica) and its Residual Biomass: Characterization for the Industrial Approach - Oliveira, Érica R.; Carvalho, Gabriel R.; Santos, Paula R.; Queiroz, Fabiana (Current Nutrition & Food Science, 2020)
Background: The increase in the production of green coffee oil by pressing has generated as a residue the press cake or biomass, whose characterization allows the evaluation of its potential as a source of extracts rich in nutrients and bioactive compounds. Objective: The objective of this study was to assess the green coffee beans quality and its relation to the by-product (biomass) obtained from the beans mechanical pressing to obtain oil (generated by the oil industry), making information available on the effect of the pressing process on the biomass characteristic. Methods: Soluble solids, bulk density, pH, acidity, nutritional value, sugar, wall components, enzymatic activity, caffeine, chlorogenic acids, tannins, and total phenolic content were carried out. Results: By comparing the composition of the green beans and biomass, it could be observed that many compounds (protein, fiber, ash) were not extracted by the mechanical pressing process, in which the oil is removed but with a very low yield (< 20%). There was a reduction in the enzymatic activity of PPO (21.16 U g-1), POD (3.18 U g-1), and PG (7.39 U); PME (17281.9 U g-1) showed an increase in its activity in the biomass; lipase activity was not statistically altered. The results indicated the potential of the biomass to obtain products based on caffeine (0.9%), chlorogenic acids (11.66 mg L-1), phenolic compounds (131.1 mg 100 g-1), and oil (6.27%). Conclusion: The green coffee beans biomass is still a rich source of nutrients that could be exploited by the industry.
Keywords: Coffea arabica